We have a boolean function

Defined as F=A’B’C’+A’B’C+AB’C’+AB’C
According to Boolean Identitities and laws:
Using the rules A+A’=1 and A+A=A we get
F=A’B’(C’+C)+AB’(C’+C)
F=A’B’(1)+AB’(1) using the rule A(1)=A
F=A’B’+AB’
Using the distributive rule A(B+C)= AB+BC
B’(A’+A) Using the A+A’=1 rule
B’(1) Using the rule A(1)=A
Final simplified expression is B’
The logic gate diagram for this function would be:

@Tina The question was to simplify the boolean expression, F=A’B’C’+A’B’C+AB’C’+AB’C
then draw a logic gate diagram for F=A’B’C’+A’B’C+AB’C’+AB’C

What is the question